Cardiovascular Changes in Patients With COVID-19 From Wuhan, China - Song, Limin; Zhao, Shuai; Wang, Li; Yang, Kai; Xiao, Weimin; Clifford, Sean; Huang, Jiapeng; Chen, Xiangdong (Frontiers in Cardiovascular Medicine, 2020)
Background: COVID-19 is rapidly spreading and resulting in a significant loss of life around the world. However, specific information characterizing cardiovascular changes in COVID-19 is limited. Methods: In this single-centered, observational study, we enrolled 38 adult patients with COVID-19 from February 10 to March 13, 2020. Clinical records, laboratory findings, echocardiography, and electrocardiogram reports were collected and analyzed. Results: Of the 38 patients enrolled, the median age was 68 years (IQR, 55-74) with a slight female majority (21, 55.3%). Nineteen (50.0%) patients had hypertension. Seven (33.3%) had ST-T segment and T wave changes, and four (19%) had sinus tachycardia. Twenty (52.6%) had an increase in ascending aorta diameter, 22 (57.9%) had an increase in left atrium size, and 28 (73.7%) presented with ventricular diastolic dysfunction. Correlation analysis showed that ascending aorta diameter was significantly associated with C-reactive protein (r = 0.4313) and creatine kinase-MB (r = 0.0414). Left atrium enlargement was significantly associated with C-reactive protein (r = 0.4377), brain natriuretic peptide (r = 0.7612), creatine kinase-MB (r = 0.4940), and aspartate aminotransferase (r = 0.2947). Lymphocyte count was negatively associated with ascending aorta diameter (r = -0.5329) and left atrium enlargement (r = -0.3894). Conclusions: Hypertension was a common comorbidity among hospitalized patients with COVID-19, and cardiac injury was the most common complication. Changes in cardiac structure and function manifested mainly in the left heart and ascending aorta in these patients. Abnormal ascending aorta and left atrium size were found to be associated with severe inflammation and cardiac injury. Alternatively, ascending aortic dilation and left atrial enlargement might be present before infection but characterized the patient at risk for SARS-CoV-2 infection.